1992
DOI: 10.1063/1.108208
|View full text |Cite
|
Sign up to set email alerts
|

Filtered arc deposition of amorphous diamond

Abstract: A cathodic arc with beam filter is employed for the deposition of hydrogen-free amorphous carbon films. A linear filter is used to prevent macroparticles and nonionized carbon atoms from reaching the substrate. The deposited films are characterized by their optical and mechanical behavior. Depending on the deposition conditions, optical band gaps in the range 2.1–2.4 eV are measured. Mechanical properties are investigated using the nanoindentation method and are shown to approach those of natural diamond. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Highly tetrahedrally bonded ta-C films have also been deposited using laser initiated vacuum arcs, and pulsed cathodic arcs, 7,8 and hydrogenated ta-C films deposited using a plasma beam source. 9 There is much interest in all of these films due to their unique mechanical properties.…”
mentioning
confidence: 99%
“…Highly tetrahedrally bonded ta-C films have also been deposited using laser initiated vacuum arcs, and pulsed cathodic arcs, 7,8 and hydrogenated ta-C films deposited using a plasma beam source. 9 There is much interest in all of these films due to their unique mechanical properties.…”
mentioning
confidence: 99%
“…It is believed that a broad intermixed region which forms between the substrate and the film is responsible for the observed good adhesion properties. Cathodic arc plasma deposition of TiN films [ 10,111 and (hydrogen-free) hard amophous carbon films [12,13] have been up to now the most successful applications of the method.…”
Section: Cathodic Arc Plasma Depositionmentioning
confidence: 99%
“…[20,21] There are large variations even within each class of materials, depending on the method and parameters of deposition. Diamond-like carbon films can be synthesized by argon sputter deposition using a graphite target [12,22] [6,16,20,21]. Research over the last years has identified filtered cathodic arc deposition as one of the promising techniques for hard carbon films thinner than 5 nm [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous carbon films (a-C) that have more than 80% tetrahedral (sp 3 ) bonding are referred to as tetrahedral amorphous carbon (ta-C) [7,9,19], or sometimes even as "amorphous diamond." [20,21] There are large variations even within each class of materials, depending on the method and parameters of deposition. Diamond-like carbon films can be synthesized by argon sputter deposition using a graphite target [12,22] [6,16,20,21].…”
mentioning
confidence: 99%